(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This work presents and investigates a new class of meromorphically uniformly convex functions with positive coefficients that a differential operator defines. It also derives properties such as coefficient bounds, distortion properties, δ-neighborhoods, convex linear combination, and convolution properties.